MENGURAI AKAR PERMASALAHAN KETIDAKLANCARAN PERKALIAN PADA SISWA KELAS TINGGI SEKOLAH DASAR: SEBUAH TINJAUAN LITERATUR - Miftahul Izzah Filhayati; Melisa Zahara; Muhammad Ahlul; Ari Suriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Multiplication fluency among upper-grade elementary school students remains a problem in mathematics learning. Students who are not fluent in multiplication often face difficulties in solving long multiplication, division, fractions, area problems, and word problems. This article aims to examine the root causes of multiplication disfluency among upper-grade elementary school students through a literature review. The method used is a qualitative approach with library research, which involves reviewing journal articles, books, and educational documents related to elementary mathematics learning, multiplication operations, learning difficulties, instructional media, and students’ psychological factors. The findings show that multiplication disfluency is not only caused by weak memorization of multiplication tables, but is also related to weak conceptual understanding, limited mastery of basic multiplication facts, procedural errors, low accuracy, irregular practice, limited variation in instructional media, and mathematics anxiety. Effective multiplication learning needs to combine conceptual strengthening, the use of concrete and visual media, gradual practice, educational games, counting strategies, and a classroom atmosphere that supports students’ courage to try. This review indicates that multiplication fluency should be developed through a balanced process involving understanding, practice, strategy, and support from the learning environment.